2021
DOI: 10.1186/s12913-021-07103-x
|View full text |Cite
|
Sign up to set email alerts
|

‘Fix the issues at the coalface and mental wellbeing will be improved’: a framework analysis of frontline NHS staff experiences and use of health and wellbeing resources in a Scottish health board area during the COVID-19 pandemic

Abstract: Background Frontline healthcare staff working in pandemics have been reported to experience mental health issues during the early and post-peak stages. To alleviate these problems, healthcare organisations have been providing support for their staff, including organisational, cognitive behavioural and physical and mental relaxation interventions. This paper reports the findings of a study commissioned by a Scottish NHS health board area during the initial outbreak of COVID-19. The study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
4
7
0
Order By: Relevance
“…The present study found that, although mental well-being resources were available, their level of uptake was hampered by lack of awareness, issues with access and skepticism of their utility. In line with the present study, lack of time, among other access issues, has been highlighted as a major barrier to the use of health and well-being services in other NHS institutions [ 41 , 42 ]. The present study has highlighted this as an area for further improvement within an NHS cancer center.…”
Section: Discussionsupporting
confidence: 85%
“…The present study found that, although mental well-being resources were available, their level of uptake was hampered by lack of awareness, issues with access and skepticism of their utility. In line with the present study, lack of time, among other access issues, has been highlighted as a major barrier to the use of health and well-being services in other NHS institutions [ 41 , 42 ]. The present study has highlighted this as an area for further improvement within an NHS cancer center.…”
Section: Discussionsupporting
confidence: 85%
“…NHS support for staff mental health and wellbeing was expanded during the pandemic ( 105 ), however a study in Scotland ( 3 ) found that barriers prevented their use for many staff. Although they focussed on front line staff, the key barriers highlighted are likely the same for laboratory workers, e.g., heavy workload, low staffing, and a fear of being judged ( 3 , 110 ). They suggest it’s not enough just to have support resources in place, but organisational plans to allow staff to access resources are required.…”
Section: Post-pandemic Laboratory Training and Assessmentmentioning
confidence: 99%
“…The global impact of COVID-19 and past pandemics on mental health and wellbeing has been well documented (1,2), particularly in patient facing healthcare professionals such as doctors and nurses (3)(4)(5)(6)(7). There is also increasing research regarding the impact on students (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…More accurately, perhaps, wellbeing priorities have drifted back to concerns surrounding long-term workplace aggravations. 7 Individual interventions have been curtailed as funding, and the will to persevere with time-consuming self-care processes, have dried up. Exhaustion, redeployment, chronic lack of staffing, basics such as lack of parking and the loss of initially overwhelming executive and public support now compound wellbeing fatigue; entrenched issues ‘at the coalface’ stubbornly persist.…”
Section: A Clinician’s Perspective: Dr Rowena Clarkmentioning
confidence: 99%